Interictal psychosis following temporal lobe surgery: dentate gyrus pathology. Issue 14 (8th April 2014) - Thom, M.; Kensche, M.; Maynard, J.; Liu, J.; Reeves, C.; Goc, J.; Marsdon, D.; Fluegel, D.; Foong, J.
Abstract : Background: De novo interictal psychosis, albeit uncommon, can develop in patients following temporal lobe surgery for epilepsy. Pathological alterations of the dentate gyrus, including cytoarchitectural changes, immaturity and axonal reorganization that occur in epilepsy, may also underpin co-morbid psychiatric disorders. Our aim was to study candidate pathways that may be associated with the development of interictal psychosis post-operatively in patients with hippocampal sclerosis (HS). Method: A total of 11 patients with HS who developed interictal psychosis (HS-P) post-operatively were compared with a matched surgical HS group without psychosis (HS-NP). Resected tissues were investigated for the extent of granule cell dispersion, mossy fibre sprouting and calbindin expression in the granule cells. We quantified doublecortin, mini-chromosome maintenance protein 2 (MCM2) and reelin-expressing neuronal populations in the dentate gyrus as well as the distribution of cannabinoid type 1 receptor (CBR1). Results: The patterns of neuronal loss and gliosis were similar in both groups. HS-P patients demonstrated less mossy fibre sprouting and granule cell dispersion ( p < 0.01) and more frequent reduction in calbindin expression in granule cells. There were no group differences in the densities of immature MCM2, doublecortin and reelin-positive cells. CBR1 labelling was significantly lower in Cornu ammonis area CA4 relative to other subfields ( p < 0.01); although reduced staining in all hippocampal regions was noted in HS-P compared with HS-NP patients, the differences were not statistically significant. Conclusions: The alterations in dentate gyrus pathology found in HS-P patients could indicate underlying differences in the cellular response to seizures. These mechanisms may predispose to the development of psychosis in epilepsy and warrant further investigation.